THE SCIENTIFIC APPROACH AND DEVELOPMENT OF STUDENTS' SCIENTIFIC ATTITUDES AT STATE ELEMENTARY SCHOOL (SDN) OF DEMANGAN YOGYAKARTA - Ratih Sukmawati; Siti Fatonah (Sunan Kalijaga International Journal on Islamic Educational Research, 2018)
The purpose of this research is to describe and analyze how the scientific approach and the development of students' scientific attitude in the thematic content of 2013 curriculum implementation. This type of research is qualitative research. Data are collected by using observation, interview, and documentation. This study intends to gain an understanding of the relevant facts about the application of the scientific approach to develop students' scientific attitude in the thematic teaching subject. The results of this research showed that the State Elementary School Demangan (SDN) of Yogyakarta has begun to implement 2003 curriculum in the grade 1 and 4 since 2014 to date, but the implementation has stopped in 2015 because the curriculum 2013 has slightly changed. The process of learning in the classroom is currently running quite well. Teachers provide feedback well, develop student curiosity, discussion, give positive reinforcement, appreciation and also reflection together that ended by the conclusion. The students' scientific attitude that appears is a high curiosity characterized by the emergence of questions containing curiosity, their responsibilities in completing tasks, their efforts to discuss group and presentation in front of the class, respect for others, cooperation, courage, critical thinking and open. The learning activities are implicated in the implementation stage of the scientific approach. Finally, the implementation of the curriculum 2013 approach essentially develops students' scientific attitude, not only on the content of science but also other content, known as the thematic content.